Peran Humas dalam Pelaksanaan Program Penurunan Angka Kematian Bayi Kabupaten Banyumas - Leony, Anastasia; Prastyanti, Shinta; Setiansah, Mite (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The Infant Mortality Rate (IMR) in Banyumas Regency continued to showed fluctuacting trend from 2017-2023, thus requiring more attention. This condition has prompted the Banyumas Regency Government to continuously make various efforts to curb the rising IMR in the future. These efforts are implemented through various programs to create understanding from the Banyumas Regency Health Office to the public. In executing these programs, there are public relations strategies used to support the optimal implementation of the programs. Each program has different objectives and target groups. This is based on the awareness that to control the Infant Mortality Rate, the government cannot focus on one target alone. Not only to create understanding among the public, but coordination among various health agencies is also important. This study aims to describe how public relations roles are utilized in each program that has been implemented to reduce the Infant Mortality Rate. This study uses a qualitative descriptive research method with case study data analysis. The data analyzed are derived from documents of Banyumas Regency reports from 2017-2023, supported by other written documents from various sources. The results indicate that in maximizing the process of reducing and preventing the increase in Infant Mortality Rate, the Banyumas Regency government utilizes public relations roles in various forms. The utilization of various public relations activities is adjusted to the objectives of each program, both online and offline.